The extract of the jellyfish Phyllorhiza punctata promotes neurotoxic effects - Vasconcelos Carneiro, Raquel Felipe; Falcao do Nascimento, Nilberto Robson; Correia Costa, Paula Priscila; Gomes, Victor Martins; Felizardo de Souza, Alex Jardelino [UNESP]; Buzzo de Oliveira, Simone Cristina [UNESP]; dos Santos Diz Filho, Eduardo Britto [UNESP]; Zara, Fernando Jose [UNESP]; Fonteles, Manasses Claudino; Toyama, Daniela de Oliveira; Toyama, Marcos Hikari [UNESP]; Santos, Claudia Ferreira (Wiley-Blackwell, 2011)
Phyllorhiza punctata (P. punctata) is a jellyfish native to the southwestern Pacific. Herewith we present the biochemical and pharmacological characterization of an extract of the tentacles of P. punctata. The tentacles were subjected to three freezethaw cycles, homogenized, ultrafiltered, precipitated, centrifuged and lyophilized to obtain a crude extract (PHY-N). Paralytic shellfish poisoning compounds such as saxitoxin, gonyautoxin-4, tetrodotoxin and brevetoxin-2, as well as several secretory phospholipase A2 were identified. PHY-N was tested on autonomic and somatic neuromuscular preparations. In mouse vas deferens, PHY-N induced phasic contractions that reached a peak of 234 +/- 34.7% of control twitch height, which were blocked with either 100 mu m of phentolamine or 1m m of lidocaine. In mouse corpora cavernosa, PHY-N evoked a relaxation response, which was blocked with either L-NG-Nitroarginine methyl ester (0.5 m m) or 1m m of lidocaine. PHY-N (1, 3 and 10 mu g ml(-1)) induced an increase in tonus of the biventercervicis neuromuscular preparation that was blocked with pre-treatment of galamine (10 mu m). Administration of 6 mg kg(-1) PHY-N intramuscularly produced death in broilers by spastic paralysis. In conclusion, PHY-N induces nerve depolarization and nonspecifically increases neurotransmitter release. Copyright (C) 2011 John Wiley & Sons, Ltd.
Keywords: Neurotoxicity; marine neurotoxic alkaloids; neuromuscular blockade; smooth muscle spasm; spastic paralysis; nitrergic stimulation